ACHIEVING VALUE FROM ICT IN SMES: KEY MANAGEMENT STRATEGIES - Johnston, K.; Parker, S.; Tu, K.D.; Mosoval, F. (Institute of Research and Community Outreach - Petra Christian University, 2009)
ICT covers a broad range of fields in business and therefore makes ICT value difficult to simply define. The main factors that influence the use of ICT are therefore important to look at, as they give a good understanding of the how much influence the organisation has, on achieving value in its given context. The transformational model of ICT use was analysed to establish how SMEs in South Africa achieve business value from ICT and what management practices are most effective. Implications of the research are that management practices are an important factor that influences the value from ICT, and that the more management practices organisations implement, the greater the business value from ICT. Further findings of this study deduced that organisations that are more ICT aware, gain greater business value from ICT, with value achievement from ICT largely within the organisation’s control. This paper concludes with recommendations for future research.